The Integration Strategy of Conservation Values in Habituation of Semarang State University Campus - Saddam Saddam; Achmad Zurohman; Babul Bahrudin (Universitas Muhammadiyah Mataram, 2018)
UNNES crowned a conservation university. The vision of UNNES to 2040 became an internationally reputable and conservation university. Conservation means the effort to protect and preserve the value of culture and human behavior in interacting with the environment. The research objectives reveal the integration of conservation values in UNNES campus habituation. The study used a qualitative case study design. Data collection using observations, documentation, and interviews. Testing the validity of data using the triangulation of sources, techniques, and theories, using the social action theory Talcott Parsons and the personality theory of Gordon Allport. Data analysis uses the Miles and Huberman models through three stages; Data reduction, data presentation, and data verification, as well as Spradley's taxonomy analysis. The results of the integration strategy of conservation values in the habituation of UNNES campus are conducted through academic and non-academic activities. Through academic activities, it is seen from the planting of conservation values through conservation education, environmental education, and other courses. While through non-academic activities are seen with the planting of conservation values through UPT conservation development activities, student activity units, and the Student Activities Center. The student personality has been conservative seen from the conservative behavior of college students, habituation to be a strategy to embed conservation values. With this, the student's behavior is closely related to the conservation character he has, so it can reflect the actions that have been performed by the role of instilling the conservation values of UNNES.